Violencia intrafamiliar y autoestima en adolescentes de la Institución Educativa Virgen del Carmen, Alto Trujillo – Trujillo 2019 - Calderón Rodríguez, Lucero Del Pilar (2020)
The research is of a descriptive correlational type, carried out during the months of November and December of 2019, at the Virgen del Carmen Educational Institution - Alto Trujillo, with the purpose of establishing the relationship between domestic violence: physical, psychological and sexual, and the level of self-esteem in teenagers. The sample universe consisted of 68 adolescents, two instruments were used for data collection: Self-Esteem Test and Domestic Violence Scale. Statistical analysis was performed using the Chi square test. After having carried out the analysis, the following conclusions have been formulated: The type of domestic violence that most adolescents presented was psychological violence with 88 percent, followed by physical violence with 72 percent and sexual violence with 13 percent of the total sample. The level of self-esteem that most adolescents presented was average self-esteem with 60 percent, followed by low self-esteem with 31 percent, finally high self-esteem with 9 percent of the total sample. It is concluded that there is a significant relationship between domestic violence: physical, psychological and sexual and the level of self-esteem (p = 0.000 <0.05).